The Explanation of Low Energy Nuclear Reaction: An Examination of the Relationship between Observation and Explanation by Edmund Storms - Josephson, Brian (Journal of Scientific Exploration, 2015)
Edmund Storms’ new book is entitled “The Explanation of Low Energy Nuclear Reaction,” though, since it is far from clear that an acceptable explanation has been given in the book, a more accurate title might be “Attempting to Explain Low Energy Nuclear Reactions” (commonly known as cold fusion, and abbreviated by the acronym LENR). Storms’ strategy involves exhaustive study of the many experiments that appear to validate claims for the existence of this phenomenon, arguing on the basis of these experiments that many possibilities are excluded by the data: Hence, very few possibilities remain for consideration.